Self-medication with antibiotics in Saudi Arabia - Sultan Alghadeer; Khalid Aljuaydi; Salmeen Babelghaith; Abdullah Alhammad; Mohammed N. Alarifi (Elsevier, 2018)
Introduction: Despite of the global dilemma of antibiotics resistance, this issue is more worsen in developing countries or places where the antibiotics can be dispensed or purchased without prescription such as in Saudi Arabia. Most health awareness campaigns and published studies regarding the self-medication with antibiotics in Saudi Arabia are conducted within hospitals. The prevalence and reasons of self-medication with antibiotics were not well studied from community perspective in Saudi Arabia. This study was conducted to investigate the prevalence of self-medication with antibiotics in Saudi Arabia. Methodology: A cross-sectional study using online survey and snowball technique was conducted during the period from January 2017 to May 2017 targeting people who are living in Saudi Arabia. Results: A total of 1264 respondent completed the questionnaire and included in the study. About 34% of respondents have used antibiotic without a prescription, and 81.3% of them knew that it might be harmful to health. The most antibiotic used for self-medication was Amoxicillin/clavulanic acid (45.1%) followed by amoxicillin (39.9%). The most common illness and reasons for seeking antibiotic without prescription were tonsillitis (76.7%) and the previous experience of using a particular antibiotic (52.1%) respectively. The major source of self-medication with antibiotic was previous doctor's prescription (36.6%). Conclusion: The relative high prevalence of self-medication with antibiotics necessitates taking serious steps by health authorities to implement the law of forbidding the sale of antibiotics without prescription. Keywords: Self-medication, Antibiotics, Without prescription, Saudi Arabia